Acute Lymphoblastic Leukemia, Classification, Clinical features and Diagnosis - Kadhim Ibrahim AL- Mahdawi, Fatimah; Razooqi Mohammed , Mazin (Diyala Journal of Medicine, 2020)
Background: Leukemias are classified as lymphoid or myeloid, dependent on the type of stem cell that is affected. In addition, leukemia is classified as chronic or acute. Acute leukemia is a production of bone marrow-derived immature cells (blasts), include solid organs or peripheral blood. The FAB Cooperative Group original classification scheme proposed to divide1 ALL into three subtypes (L1 - L3). Currently, the world health organization (WHO), modify FAB classification depending on immunophenotype. Symptoms presence of anemia, splenomegaly, and thrombocytopenia, and those are naturally present at diagnosis, indicating the degree to which leukemic lymphoblasts have replaced the bone marrow and the first mark to an ALL diagnosis is typically an abnormal complete blood count result. Objective: To introduce causes of acute lymphocytic leukemia, recent classification methods, diagnosis, and symptoms and diagnosis. Conclusion: Acute lymphocytic leukemia occurs due to a defect in the bone marrow and is classified into several types. The most important classification by the World Health Organization is depending on immunophenotype. The main symptoms are the increase in white blood cells with anemia and thrombocytopenia.